2022
DOI: 10.1101/2022.01.24.477572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability in sampling of cortex-wide neural dynamics explains individual differences in functional connectivity and behavioral phenotype

Abstract: Individual differences in behavior are associated with changes in the correlation of neural activity between brain areas. Such differences in 'functional connectivity' are thought to reflect individual differences in brain structure that alter the flow of neural activity between regions. Here, in contrast, we show that individual differences in functional connectivity and behavior can be explained by differences in how frequently an individual expresses distinct cortex-wide spatiotemporal patterns of neural ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 45 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Each mouse was recorded twice for a total of n=6 recordings. Previous studies in animals expressing GCaMP under the Thy1 promoter have not shown epileptiform activity 5,35 . Consistent with this, we screened all recordings for potential epileptiform activity and no events were observed.…”
Section: Micementioning
confidence: 76%
See 4 more Smart Citations
“…Each mouse was recorded twice for a total of n=6 recordings. Previous studies in animals expressing GCaMP under the Thy1 promoter have not shown epileptiform activity 5,35 . Consistent with this, we screened all recordings for potential epileptiform activity and no events were observed.…”
Section: Micementioning
confidence: 76%
“…Altogether, the 14 motifs captured 65.8% of the variance in cortex-wide neural activity in withheld data (CI: 65.0-66.6%). Importantly, which motif was expressed changed on a moment-by-moment basis 4,5 , reflecting flexibility in how neural activity propagated between brain regions during spontaneous behaviors.…”
Section: Flow Of Activity Between Brain Areas Is Associated With Alig...mentioning
confidence: 99%
See 3 more Smart Citations